Decreases in mRNA by an siRNA Complex Do not Alter Blood Pressure in Mice - Su-Min Ji; Young-Bin Shin; So-Yon Park; Hyeon-Ju Lee; Bermseok Oh (Genomics & Informatics)
Recent genomewide association studies of large samples have identified genes that are associated with blood pressure. The Global Blood Pressure Genetics (Global BPgen) and Cohorts for Heart and Aging Research in Genome Epidemiology (CHARGE) consortiums identified 14 loci that govern blood pressure on a genomewide significance level, one of which is CASZ1 confirmed in both Europeans and Asians. CASZ1 is a zinc finger transcription factor that controls apoptosis and cell fate and suppresses neuroblastoma tumor growth by reprogramming gene expression, like a tumor suppressor. To validate the function of CASZ1 in blood pressure, we decreased Casz1 mRNA levels in mice by siRNA. Casz1 siRNA reduced mRNA levels by 59% in a mouse cell line. A polyethylenimine-mixed siRNA complex was injected into mouse tail veins, reducing Casz1 mRNA expression to 45% in the kidney. However, blood pressure in the treated mice was unaffected, despite a 55% reduction in Casz1 mRNA levels in the kidney on multiple siRNA injections daily. Even though Casz1 siRNA-treated mice did not experience any significant change in blood pressure, our study demonstrates the value of in vivo siRNA injection in analyzing the function of candidate genes identified by genomewide association studies.